Analysis of Students' Creative Thinking Skills in Mathematics Learning with The Application of Ethnomathematics of Batik Sendang - Malik, Fatus Atho'ul (Mathematics Education Study Program, 2024)
One important aspect of education in the 21st century is developing students' creative thinking skills. The development of creative ideas is usually related to a person's socio-cultural. One of the cultural heritages in Lamongan is batik Sendang. Batik Sendang motifs can make students to explore, so that students can grow their creativity. Therefore, ethnomathematics plays an important role in connecting culture with mathematics learning to foster student creativity. This research aims to analyze and describe students' creative mathematical thinking skills in solving problems designed with the application ethnomathematics batik Sendang. The subjects of this research consisted of four students in class IX at MTs Tarbiyatus Shibyan Lamongan who were classified according to the criteria for creative thinking skills, namely low, medium, high, and very high. The results of this research show impressive things. That is 70.59% of students show high to very high creative thinking skills. Meanwhile 29.41% of students show low and medium creative thinking skills. It is hoped that the results of this research can help researchers and teachers to determine measuring tools or methods to improve students' creative thinking skills, one of which is ethnomathematics of batik Sendang.